Bank bailout programs in Europe: a sequential analysis of drivers and outcomes - Barbu, Teodora-Cristina; Boitan, Iustina-Alina; Cepoi, Cosmin-Octavian; Dumitrescu, Bogdan Andrei (Journal of Business Economics and Management, 2021)
The determinants and effects of bank bailout programs on the economy and society are still controversial. Using a Propensity Score Matching approach relying on 22 European countries, it was identified economic growth, economic freedom, total banking assets, and liquid assets to deposits and short-term funding ratio as the main drivers for the decision to adopt a bank bailout program. The results show that the adoption of bank bailout programs did not lead to an improvement in the banks’ solvency indicators or financial performance. Still, it has amplified financial stress and income inequality instead, hampering political stability, as well as social and economic conditions. The novelty of this research resides in adding a contribution to scarce literature covering the determinants of the decision to adopt a bank bailout program, also by comprehensively expanding the set of candidate variables that may have impacted the decision for Government intervention.